Smart Cities: A Vision for Future Cities (International Journal of Innovative Research in Engineering & Management, 2022)
It is been observed and evident by many  scholars around the world that today 50% of the world  population lives in urban centres. The study of population  growth rate indicates that if this growth rate continues in  the same way at the end of this century almost all the  people in the world will live in large cities. All the cities  face problems in terms of managing solid waste, scarcity  of resources, traffic congestion, air pollution, and  inadequate and deteriorating infrastructure. Looking at the urgency to answer such issues many cities have accepted  to grow with the idea of being smart. Thus, planning smart  cities is a new approach to mitigate the issues created in  the urban areas developing with high population growth  and concentration of the population. This paper aims to  study the smart city concept globally as well as in the  context of India and discusses the recommendations that  can be carried forward to build smart cities in India.
Keywords: Internet; Internet of Things (IOT); Smart City; Security; Technology